Bank Risk, Profitability, Dan Investment Diversification: Studi Perusahaan Perbankan Di Indonesia - Aditya Kurnia Indrajaya; Stevan Goklas Simanjuntak; Susy Muchtar (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
The aim of this study was to determine whether risk assessment, company profits, and macroeconomic factors affect the decisions of banking companies in determining investment diversification. The independent variables in this study are credit risk, liquidity risk, profitability, inflation rate, and gross domestic product (GDP) while the dependent variable is investment diversification. There are three control variables in this study, namely bank size, interbank ratio, LA, and capitalization ratio. This study was conducted using a data sample of 41 banking companies listed on the Indonesia Stock Exchange (IDX) within a reporting period of 5 years (2016 – 2020) and using panel data regression model testing. The results of this study indicate that liquidation risk and credit have a negative effect, while the inflation rate and GDP have a positive effect on investment diversification. The results of this study can help bank financial management to manage investment diversification strategies by paying attention to risk and maximizing profitability. In the novelty of this study, the coefficient of variation is used to measure the dependent variable so that the measurement can be distinguished from other studies.